Promoting mechanism of SO2 resistance performance by anatase TiO2 {0 0 1} facets on Mn-Ce/TiO2 catalysts during NH3-SCR reaction. (6th April 2022) - Li, Junchen; Zhang, Cheng; Li, Quan; Gao, Ting; Yu, Shenghui; Tan, Peng; Fang, Qingyan; Chen, Gang
Highlights: The SO2 resistance and mechanism of Mn-Ce/TiO2 -NS and Mn-Ce/TiO2 -NP catalysts at 180 °C were revealed by characterization and DFT analysis. Preferentially exposing {0 0 1} facets of anatase TiO2 can effectively inhibit the formation of ammonium sulfate and ammonium bisulfate. The Ti5c and O2c atoms on the {0 0 1} surface of anatase titanium dioxide are easier to react with SO2 to form titanium sulfate, which is beneficial to protect the active components such as Mn and Ce. Abstract: Anatase TiO2 with {0 0 1} facets (TiO2 -NS) exposed and anatase TiO2 with {1 0 1} facets (TiO2 -NP) exposed as carrier were used to prepare Mn-Ce/TiO2 -NS and Mn-Ce/TiO2 -NP catalysts, separately. The Mn-Ce/TiO2 -NS catalyst still had a high specific surface area after the SO2 resistance test, which was attributed to the inhibition of the formation of ammonium bisulfate and ammonium sulfate. Additionally, anatase TiO2 {0 0 1} surface could effectively inhibit the sulfation of active ingredients, which was owing to the five-coordinated titanium atoms (Ti5c ) and two-coordinated oxygen atoms on the anatase TiO2 {0 0 1} facets could preferentially react with SO2 to avoid deactivation of active sites after the poisoning experiment. Thus, the Mn-Ce/TiO2 -NS catalyst had excellent resistance to SO2 in the poisoning test, indicating that it has great application prospects as a low-temperature SCR catalyst.